Pengaruh Pengeluaran Pemerintah Bidang Pendidikan, Pertumbuhan Ekonomi Dan Kemiskinan Terhadap APM (Angka Partisipasi Murni) di Indonesia - Devliana Aurellin; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to determine the effect of government spending on education, per capita income and poverty on net enrollment rates in Indonesia. This research is descriptive and associative. The data used is secondary data from 33 provinces in Indonesia in 2014-2021 obtained from related agencies. This study uses panel data regression with the Random Effects Model approach assisted by Eviews 9 software. The variables used are high school enrollment rates (Y), government spending on education (X1), per capita income (X2), poverty (X3). The results of the study show that (1) government spending on education has a positive and significant effect on net enrollment rates at the high school level in Indonesia (2) per capita income has a positive and significant effect on net enrollment rates at the high school level in Indonesia (3) Poverty as a measure of the percentage of poor people has a negative and significant effect on net enrollment rates for secondary schools in Indonesia